TYPOLOGY OF EVALUATION SPEECH ACTS - Приходько, Г. І. (Zapiski z romano-germansʹkoï fìlologìï, 2020)
The given research is dedicated to the study of typology of evaluation speech acts. In this article questions connected with the analysis of the appearance of the evaluation in the utterance are being discussed. Particular attention is paid to the illocutionary and perlocutionary effect of evaluation speech acts. The purpose of the given article is to consider the most common features of evaluative speech acts and determine their place in the hierarchy of speech acts in general. The research methods, used in the study, are determined by the purpose, theoretical direction of the article and are comprehensive. The research methods integrate the basic notions of modern cognitive theory and theory of communication. The minimum unit of communication is speech act. The structure of the speech act includes four levels. They are locution, proposition, illocution and perlocution. In the evaluation speech acts, semantic basis is the category of evaluation. The author of the article offers the following classification of evaluation speech acts. Based on semantic and pragmatic properties of the object of our study, the article proposes to distinguish the following types of evaluation speech acts: 1) focus on the subject; 2) focus on the object. Among evaluation speech acts, oriented on the object, proper evaluation speech acts (for example, praise, condemnation) and emotional evaluation speech acts (for example, admiration, anger, respect) can be selected. The given approach is based on the fact that the evaluative verbs are direct representatives of illocutionary intention of evaluation speech acts. So, we consider that the classification of evaluation speech acts can rely on semantic and pragmatic features of evaluative verbs.